Science and Technology Improvement Viewed from Islamic Education - Adi Sudrajat; Asmuni Asmuni (Journal of Research in Islamic Education, 2019)
The role of teachers and parents in instilling faith and piety is very necessary to direct students in overcoming some of the effects of the progress of science and technology that is happening today. The results showed that the students of class XI MA Ma'arif Roudlotut Tholibin Metro, that the progress of science and technology in the use of learning media can be implemented quite well, can support teaching and learning outcomes in accordance with existing rules, teachers have provided as much guidance as possible about the positive impact negative and consequences of science and technology for students who violate. However, there are still some students who abuse the internet for things that are not good, environmental factors that influence children's thinking patterns to act as they please, because the school cannot supervise each student outside the school. So that the cooperation of teachers and parents is needed to form good character for students